{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

L14 Part 1 6.4.4 Miller'sTheorom_1

# L14 Part 1 6.4.4 Miller'sTheorom_1 - EE 311 EEO 311 Lecture...

This preview shows pages 1–8. Sign up to view the full content.

EE 311 & EEO 311 Lecture 14 Part 1 6.4.4 Miller’s Theorem Zubair Rehman

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
2 I 1 = Y(V 1 - V 2 ) I 1 = Y 1 V 1 I 2 = Y(V 2 - V 1 ) I 2 = Y 2 V 2 We must be able to relate V 2 & V 1 V 2 = KV 1 & V 1 = 1 / K V 2 I 1 = Y(V 1 - KV 1 ) I 2 = Y(V 2 - 1 / K V 2 ) I 1 = V 1 [Y(1-K)] I 2 = V 2 [Y(1- 1 / K )] Y 1 = Y(1-K) Y 2 = Y(1- 1 / K ) Figure 6.15 The Miller equivalent circuit. (Sedra/Smith)
3

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
4 R s Thevenin Equivalent Resistance Includes Bias Resistances & Output Resistance of previous stage. V s Thevenin Equivalent Source R L Thevenin Equivalent Load Includes Bias Resistance & Input Resistance of the next stage. From Sedra/Smith 4 th  edition
5 Note: Figure 6.20 in Sedra/Smith 5 th ed.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
6 Note: Figure 6.25 in Sedra/Smith 5 th ed.
7 V S Thevenin Equivalent Source Voltage R S Thevenin Equivalent Resistance Includes Bias Resistors, Output Resistance of Previous Stage R L Thevenin Equivalent Resistance Includes Bias Resistors, Input Resistance of Next Stage R L ’ = R L || r O where r O = (V A / I C ) BJT CE Amplifier V TH = V s * [r π / (R s + r x + r π )] = Open-Circuit Voltage R TH = r π || (r x + R s ) = Resistance with V s = 0

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}